Retrospective case study of risk factors, clinical features and laboratory parameters of peptic ulcer disease in pediatric patients - Gaevskaya, Yeuheniya; Mathotaarachchi, Bihara Rasanjalee; Yahathugoda, Dilmi Raveena (International Journal of Contemporary Pediatrics, 2025)
Background: Peptic ulcer disease (PUD) is uncommon in children, yet recognizing risk factors like age, gender and acute illness is crucial. While often in the duodenum, ulcers can also occur in the stomach. Helicobacter pylori is a primary cause of childhood PUD. Complications include bleeding, perforation and penetration. Chronic disease can alter laboratory parameters. Treatment involves H. pylori eradication and sometimes surgery. Methods: This observational retrospective study analyzed electronic medical data from 74 pediatric patients with gastric and/or duodenal ulcers at Health Care Institution-Grodno Regional Children’s Clinical Hospital, Belarus (2019-2025). We examined occurrence features, clinical presentation, etiology, complications, laboratory changes and treatment. Results: Common PUD risk factors were identified. Duodenal ulcers predominated (77%). Anatomic localization was compared. Etiologies included H. pylori, stress from chronic disease, diet, long-term hormonal therapy or were unknown. Complications included bleeding and perforation and treatment modalities were determined. Conclusions: In conclusion, it can be noted that peptic ulcers in the group of patients occurred mainly in boys over 10 years old living in the city. According to localization, in most cases, there was an acute ulcer of the duodenal bulb. The leading role in the etiology of ulcers is played by the bacterium Helicobacter pylori, dietary habits and stress. The most common complication was bleeding which needed prompt management. Several laboratory indicators were altered in these patients.